Fraksinasi dan Karakterisasi Fosfolipid dari Biji Nyamplung (Calophyllum inophyllum) (PhospholipidFractination and Characterisation of Calophylluminophyllum Kernel) - Putri, Desiana Nuriza; Hidayat, Chusnul; Hastuti, Pudji (UPN VETERAN JAWA TIMUR, 2018)
Abstract The aim of this research is to obtain the Phospholipid characteristic of Calophylluminophyllum which is suitable with the need by means of fractination process.Phospholipidcharacterisation resulted from fractination will generate recommendation of Phospholipidfractination use on suitable product and food processing. The extraction process was performed by using chloroform-methanol (1:2 v/v). The polar lipid is separated by using ethanol, then ethanol is used to extract Phospholipid. Fractination was performed based on the soluability in ethanol and acetone. There were 5 Phospholipid fraction namely crude Phospholipid (without fractination), ethanol soluble, ethanol insoluble, ethanol-acetone insoluble fraction. Each fraction was characterised for phosphatidylcholine content (PC), hydrophilic-lipophilic balance (HLB), peroxide value, viscosity and color. The result showed that the highest PC content was found on ethanol-soluble fraction, whereas highest fatty acid which arrange Phospholipid werepalmitat (C16:0) and Oleat (C:18). Phospholipid fraction which is suitable to be used as oil in water emulsifier is ethanol soluble fraction, and ethanol insoluble fraction is used as water in oil emulsifier. Keywords: Calophylluminophyllum kernel, phosphatidylcholine, phospholipid, phospholipid characteristic